Effective Voice-Based Vibration Patterns for Tactile Interfaces - Kobayashi, Daiji; Washio, Shun (Human Interface and the Management of Information: Information, Knowledge and Interaction Design, 2017)
Vibration patterns are used for presentation by tactile interfaces such as those of mobile phones. Our previous research clarified the perceptual characteristics of perceivable vibration patterns for the elderly. Then, we proposed application software for creating on/off controlled vibration patterns by tapping the touch screen of a smartphone to enable the user to create identifiable customized vibration patterns. Although Japanese elderly persons found the user interface difficult to use because of their reduced motor ability, our study concluded that the vibration patterns characterized by the pronunciation of the message were easily recognizable by users regardless of their age. This prompted us to develop an easy way to create vibration patterns based on the user’s speech. The voice-based vibration pattern, which includes characteristics of the user’s pronunciation, was more effective from the viewpoint of the memorability and learnability of the vibration pattern. However, the memorability of a voice-based vibration pattern could be reduced by specific characteristics of pronunciation such as monotonous speech. Hence, this study proposes two additional types of modified voice-based vibration patterns by emphasizing the characteristics of the user’s pronunciation. Further, these two new types of vibration patterns were evaluated experimentally in comparison with the conventional type from in respect of memorability. As a result, we found that the user’s pronunciation and/or recognition ability rather than the characteristics of the type of vibration patterns could affect the user’s performance.